Sheikh Omar bin Al-Hamalawi: between the religious and the political 1942-1954 - Titush, Hadah (The Algerian Historical Journal, 2026)
This article sheds light on the personality of Sheikh Omar bin Hamlawi, a descendant of the Rahmaniyya order in the Constantine prefecture, and the leader of the Hamlawiyya Zawiya in Ain El Aars (between 1942-1966). To understand his educational and economic role at the level of the Hamlawiyya Zawiya, in order to continue its mission in serving knowledge and memorizing the Holy Quran. We also aim to determine his positions and opinions on various religious and political issues that concerned Algeria in the period from 1942 to 1954, such as the issue of separating Islam from the state in Algeria, and the issue of participation in the Algerian Council elections.